The dire king eaudiobook - Ritter, William (Jackaby, 2017)
The thrilling conclusion to the New York Times best-selling series the Chicago Tribune called "Sherlock Holmes crossed with Buffy the Vampire Slayer" sends the eccentric detective and his indispensable assistant into the heart of a war between magical worlds. The fate of the world is in the hands of detective of the supernatural R. F. Jackaby and his intrepid assistant, Abigail Rook. An evil king is turning ancient tensions into modern strife, using a blend of magic and technology to push Earth and the Otherworld into a mortal competition. Jackaby and Abigail are caught in the middle as they continue to solve the daily mysteries of New Fiddleham, New England - like who's created the rend between the worlds, how to close it, and why zombies are appearing around town. At the same time, the romance between Abigail and the shape-shifting police detective Charlie Cane deepens, and Jackaby's resistance to his feelings for 926 Augur Lane's ghostly lady, Jenny, begins to give way. Before the four can think about their own futures, they will have to defeat an evil that wants to destroy the future altogether. The epic conclusion to the New York Times best-selling Jackaby series features sly humor and a quirky cast of unforgettable characters as they face off against their most dangerous, bone-chilling foe ever.